Temperature dependency in the preparation of silicon oxide (si02) layer. / Suazlina Mohd Ali - Mohd Ali, Suazlina (2011)
In the fabrication of silicon based devices, oxidation process is one of the most important stages since the thickness of oxide layer is very accountable in determining the quality of the devices. Many publications have discussed the properties and applications of silicon (Si) which were investigated from many aspects. The oxidation temperature affects silicon thickness. The oxidation temperature is one of the parameter that can be controlled in order to produce certain required properties of the oxide layer mainly the oxide thickness. Previous researches have shown that the temperature of the oxidation furnace affects the oxide growth on silicon substrate. Therefore, several researchers already showed the oxidation at higher temperature will increase the thickness of silicon oxide (SiO). A series of silicon samples are prepared with different temperature. In this project, the silicon oxide was prepared at elevated temperature but the other parameters such as oxidation time, oxygen flow rate, nitrogen flow rate, deposition pressure and crystal orientation are fixed. Two types of silicon wafer were used as substrate. They are n-type and p-type silicon of the same (10 0) orientation. The temperature of the oxidation furnace is made to be 500°C, 600°C, 700°C, 800°C, 900°C and the oxidation time for each temperature is done for 1 hour. The oxide thickness is formed to increase linearly with increase in furnace temperature. Oxidation on n-type silicon substrate is higher than that of p-type silicon substrate. The silicon oxide layer was successfully produced and the thickness of silicon samples had been measured. This study has provided useful information on the optimum parameters in preparing oxide layer especially for researchers who are using similar oxidation furnace.